Acquired immunodeficiency syndrome-related progressive multifocal leukoencephalopathy-immune reconstitution inflammatory syndrome: prevalence, main characteristics, and outcomes in a Brazilian center - Monize Nascimento Santana; Raphaela Ferrari; Arthur Cassa Macedo; Rosa Maria Nascimento Marcusso; Ruan de Andrade Fernandes; José Ernesto Vidal (Arquivos de Neuro-Psiquiatria)
Background Progressive multifocal leukoencephalopathy (PML) - immune reconstitution inflammatory syndrome (IRIS) in people living with HIV/AIDS (PLWHA) has been rarely described in low- and middle-income countries.